Omphalitis Leading to Urachitis and Acute Vascular Changes in a Buffalo Calf: An Insight into Macro and Microscopic Pathologic Changes - Deshmukh, Sidhartha; Banga, Harmanjit Singh; Thorat, Sneha; Brar, Rajinder Singh (Journal of Buffalo Science, 2016)
Omphalitis in domestic animals being considered as commonest ailment after birth, are in general, poorly reported for its uneventful recovery. Several previously reported cases endeavoured to highlight involvement of pathogenic organism in progression of the condition with little elaboration to pathologic changes occurred. Moreover, description of omphalitis in buffalo calf was never been attempted. Therefore this report intends to elaborate the pathology noted around umbilical zone in a buffalo calf possibly arisen to infectious etiology with special reference to complicated involvement of urachus, eventual haemoperitoneum and striking acute vascular changes of multi-systemic organs. Intriguingly, this report also attempted to review few recent cases of omphalitis seen in different animals along with their paramount etiologic causes.